Strengths, weaknesses, opportunities and threats of peer support among disadvantaged groups: A rapid scoping review - Kalina Mikolajczak-Degrauwe; Sybren R. Slimmen; Dylan Gillissen; Petra de Bil; Valerie Bosmans; Corrine Keemink; Inge Meyvis; Yvonne J. Kuipers (Elsevier, 2023)
Objective: To explore the current state of knowledge and evidence about peer support for various disadvantaged groups; to identify the strengths, weaknesses, opportunities, and threats of peer support to critically reflect on peer support within health and social services. Methods: A rapid scoping review was conducted according to Arksey and O'Malley's framework, aiming to identify eligible studies in PubMed, APA PsychInfo, Education Resources Information Center, Cochrane Library, Academic Search Premier, ScienceDirect, Directory of Open Access Journals, ResearchGate, WorldCat, and Google Scholar. According to Rodgers' concept analysis steps and the SWOT model, data was reported using thematic synthesis. Results: Forty-five studies were included, describing a variety of peer support initiatives among groups of young migrants and unsupervised minors, young adults with autism, people with (mental) health problems, foster/shelter families, vulnerable pregnant women, people outside the labour force, older adults, and homeless people. The strength of peer support is its positive effect on the quality of life among vulnerable people. The weakness is represented by peers both being too involved and focused on personal interest or by peers lacking expertise and knowledge. Opportunities for peer support are mutual learning, the anticipated long-term effects, and the potential to facilitate social inclusion. Culture, language barriers, drop-out rates, securing sustainability, and peers' lack of time and commitment are regarded as threats to peer support. Conclusion: Although peer support offers good outcomes for various groups of vulnerable people, the weaknesses and threats need to be considered to provide and proliferate peer support.